Analisis Implementasi Model Pembelajaran Project Based Learning dalam Kurikulum Merdeka di Sekolah Dasar - Nurlia Abd. Rahman; Andi S. W. Ningrum; Nurliyan Nurliyan; Nur Salsa Aurelya; Nur Zam-zam; Herlina Herlina; Kadek Herlina (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The implementation of the Project Based Learning (PjBL) learning model in the Merdeka Curriculum in elementary schools focuses on improving the quality of education and student learning outcomes. This study aims to examine the effect of PjBL on student learning outcomes, identify obstacles faced by teachers in its application, and formulate strategies to optimize the implementation of PjBL. The method used is Systematic Literature Review (SLR) with a qualitative descriptive approach based on meta-synthesis. The literature analyzed was 19 articles obtained from various sources such as Google Scholar, Elicit, and Semantic Scholar. The results showed that the implementation of PjBL had a significant impact on improving student learning outcomes, creativity, critical thinking skills, and collaboration skills. However, the implementation of PjBL faced several obstacles, such as time constraints, lack of supporting facilities, and the readiness of teachers and students in carrying out projects. To overcome these obstacles, strategies such as increasing teacher competence through training, providing adequate facilities and infrastructure, and flexible and realistic project planning are suggested. Thus, it can be concluded that the PjBL model can be an effective innovative learning method in improving the quality of education and student learning outcomes in elementary schools.